Inside Cover: Aggregation‐Induced Emission and Sensing Characteristics of Triarylborane–Oligothiophene–Dicyanovinyl Triads (Chem. Eur. J. 48/2016). Issue 48 (20th October 2016) - Kumar, George Rajendra; Sarkar, Samir Kumar; Thilagar, Pakkirisamy
Abstract : Triarylborane–oligothiophene–dicyanovinyl triads, representing A–D–A‐type luminogens, contain two different types of electron‐deficient units linked by electron‐rich oligothiophenes. Fine‐tuning the oligothiophene length imparted flexibility and effective electronic communication between the two acceptors, as well as produced interesting viscosity‐dependent fluorescence and aggregation‐induced emission properties. Additionally, their applications in anion sensing were evaluated. F − and CN − anions trigger two different color changes observable by the naked eye and hence, the triads act as colorimetric discriminators for fluoride and cyanide ions. More information can be found in the Full Paper by P. Thilagar et al. onpage 17215 ff.